Local pH changes triggered by photoelectrochemistry for silica condensation at the liquid-liquid interface. (10th January 2016) - Poltorak, Lukasz; Hébrant, Marc; Afsharian, Mohana; Etienne, Mathieu; Herzog, Grégoire; Walcarius, Alain
Highlights: pH was modified from 6 to 1 by photoelectrochemistry at the liquid-liquid interface. Local pH changes were monitored using a Pt microelectrode modified with iridium oxide. Silica condensation occurred at the liquid-liquid interface as a result of the pH changes. Abstract: We present here a new photoelectrochemical method for varying the pH locally to trigger silica condensation at the interface between two immiscible electrolyte solutions (ITIES). Trimethylbenzhydrylammonium cation is a photoactive compound dissolved in the organic phase. Electrochemical studies have shown a reversible transfer across the interface controlled by diffusion. Its transfer from the organic to the aqueous phase and its concomitant photo-irradiation has led to the decrease of pH, which was locally monitored by Pt microelectrode covered with iridium oxide and positioned at a distance of 1 μm from the ITIES by shearforce detection. Such local measurements of the pH were necessary as side reactions at the aqueous counter electrode were changing the bulk pH. The pH at the interface dropped from 6 to lower than 2 when photoelectrolysis was applied for 50 min. This local pH variation was then harnessed to the acidic condensation of mesoporous silica at the ITIES.